Teaching Reading by Using Inquiry Based Learning Approach to The First Semester of English Education Program - Syaprizal Syaprizal (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2017)
The objective of this study was to find out whether or not it was significantly effective to use Inquiry Based Learning in teaching reading to first semester of English Education Program . In this study, the writer proposed two hypotheses. They were null hypothesis Ho and alternative hypothesis Ha. The method applied was pre experimental with one group pre test posttest design. The population of this study was all of first semester of English Education Program which consisted of 45 students. The sample was taken through cluster random sampling. Which consisted of 20 students. The data were collected by means of test consisting 20 items of multiple choices. The data obtained were analyzed through three techniques 1 Individual Score, and 2 Matched t test. The results of this study shows that the students mean score in the pre-test was 60.13 and those in the post-test was 75.25. The result of matched t test was 5.25, which was higher than t table value 1.725 of 20 with 95 percent significant level for one tailed test. Therefore, the null hypothesis Ho was rejected and the alternative hypothesis Ha was accepted. It means that it was significantly effective to use Based Learning Approach in teaching reading to first semester of English Education Program Keyword: Teaching Reading, Using Inquiry Based Learning Approach.